Low coronary flow relative to myocardial mass predicts heart failure in symptomatic hypertensive patients with no obstructive coronary artery disease . (7th September 2021) - Brown, Jenifer M; Zhou, Wunan; Weber, Brittany; Divakaran, Sanjay; Barrett, Leanne; Bibbo, Courtney F; Hainer, Jon; Taqueti, Viviany R; Dorbala, Sharmila; Blankstein, Ron; Di Carli, Marcelo F
Abstract: Aims: The transition from hypertension to heart failure (HF) remains poorly understood. We hypothesized that insufficient perfusion to match global metabolic demand, reflected by a low ratio of myocardial blood flow to global myocardial mass, may be a HF risk marker. Methods and results: A retrospective cohort ( n = 346) of patients with hypertension who underwent clinical positron emission tomography (PET) myocardial perfusion imaging for chest pain and/or dyspnoea at Brigham and Women's Hospital (Boston, MA, USA) were studied. Patients without obstructive coronary artery disease by history or PET perfusion (summed stress score <3), HF, cardiomyopathy, or ejection fraction (EF) <40% were followed for HF hospitalization (primary outcome), all-cause death, and their composite. Myocardial blood flow, left ventricular (LV) mass, volumes, and EF were obtained from PET, and a 'flow/mass ratio' was determined as hyperaemic myocardial blood flow over LV mass indexed to body surface area. A lower flow/mass ratio was independently associated with larger end-diastolic (β = −0.44, P < 0.001) and end-systolic volume (β = −0.48, P < 0.001) and lower EF (β = 0.33, P < 0.001). A flow/mass ratio below the median was associated with an adjusted hazard ratio of 2.47 [95% confidence interval (CI) 1.24–4.93; P = 0.01] for HF hospitalization, 1.95 (95% CI 1.12–3.41; P = 0.02) for death, and 2.20 (95% CI 1.39–3.49; P < 0.001) for the composite. Conclusion: An integrated physiological measure of insufficient myocardial perfusion to match global metabolic demand identifies subclinical hypertensive heart disease and elevated risk of HF and death in symptomatic patients with hypertension but without flow-limiting coronary artery disease. Graphical Abstract: